Prostate-specific antigen as a risk factor for skeletal metastasis in native ethnic African Men with prostate cancer: A case-control study - Ayman Qureshi; Khalid Makhdomi; William Stones (World Journal of Nuclear Medicine)
Prostate cancer is the most common noncutaneous cancer in males. Men of African origin are at a significantly higher risk as reflected in the higher incidence and mortality rates in this racial group. Metastases incidence increases parallel to serum levels of prostate-specific antigen (PSA), contributing significantly to morbidity and mortality. Staging of the disease involves bone scans, which are sensitive in detecting skeletal metastases. Suggestions that these scans may be omitted in some situations in patients with low prostate specific antigen levels have drawn attention to the matter. In this case-control study, using radiology and pathology records, a registry of prostate cancer patients recorded as being of dark-skinned ethnicity was obtained. Images were presented to image reviewers blinded to the PSA level, to determine the presence of skeletal metastases. The risk factor for the outcome of interest (skeletal metastases) was PSA level above 20 ng/mL. The reliability of image reporting was also assessed. Of the 122 patients, skeletal metastases were present in 50 (41%) while these were absent in 72 (59%). The prevalence of metastases among the high PSA group was 55.9% [95% confidence interval (CI) 44.1–67.7%] and among the normal/low PSA group was 22.2% (95% CI 11.1–33.3%). The odds ratio (OR) for skeletal metastases in the exposed (high PSA) group was 4.4 (95% CI, 2.01–9.78.) Intraobserver agreement on image interpretation was 88.5% with a Kappa statistic of 0.76. A relatively higher prevalence of skeletal metastasis is seen in regional dark-skinned African males with prostate cancer at both low and high prostate specific antigen levels. Bone scanning in this population should therefore, be considered even at PSA levels below 20 ng/mL.